Peran Pemerintah Daerah dalam Pengembangan Pariwisata Alam dan Budaya di Kabupaten Tapanuli Utara - Simamora, Rotua Kristin; Sinaga, Rudi Salam (Universitas Medan Area, 2016)
The purpose of this research is to know the role of local government in developing the tourism potential of nature and cultural tours in North Tapanuli Regency. In this study the method used is descriptive qualitative approach is exemplary. The source of the data in this study there are two primary data and secondary data. The technique of data collection is done Field Research (Fieldwork) such as observation, interviews and Library research (Research Libraries). The analysis will be used by the author is descriptive qualitative. The results of research on the role the role of tourism in the development of the potential of tourism in North Tapanuli Regency is dominant as a facilitator as compared with other roles as motivators and dinamisator. The role of the facilitator is seen primarily in terms of the provision of the infrastructure objects are still largely borne by the Funds channelling aid, a stimulant for people who want to develop a tourism objects, tourism promotion efforts, as well as facilities provided on such third-party investors and entrepreneurs to develop business tourism sights in North Tapanuli Regency.